Industrial training report: Bahagian Hal Ehwal Akademik (HEA) Universiti Teknologi MARA (Kelantan) / Mohd Syahir Hakimi Zulkifli - Zulkifli, Mohd Syahir Hakimi (Perpustakaan Tengku Anis, 2017)
The student who undertakes industrial training is responsible mainly to complete the project and tasks assigned by the organization within the stipulated time frame. As we know, internships provide real world experience to those looking to explore or gain relevant knowledge and skills require entering into particular career field. Internship relatively short term in nature with the primary focus on getting some on the job training and taking what's learned in the classroom and applying it to the real world.